Analysis and design of modular open‐loop LED driver with multi‐channel output currents. Issue 7 (1st June 2019) - He, Qingqing; Luo, Quanming; Huang, Jian; Cao, Chi; Sun, Pengju
Abstract : In view of some applications for red green blue (RGB) light‐emitting diodes (LEDs), a modular multi‐channel constant‐current LED driver is getting more important to obtain desirable colour and brightness. A multi‐channel constant‐current LED driver is proposed according to the constant‐current characteristics of the passive LCL‐T resonant network, which is composed of one high‐frequency half‐bridge inverter and as many passive LCL‐T resonant rectifiers as the number of output channels. Only one passive resonant rectifier is added to increase a constant‐current output channel, thus, it is easy to achieve multi‐channel constant‐current output as needed. In practical applications, the control can be simplified and the reliability can be improved in the open‐loop mode. However, any change of input and output voltage would cause a certain fluctuation in the output current considering the high‐order harmonic components in the open‐loop mode. To this end, the precise solution of the actual output current is obtained in the paper. The quantitative parameter design has been completed according to the desirable current to meet the output constant‐current accuracy within the given input and output. Finally, a 120‐W prototype with three different constant‐current outputs is built to verify the correctness of theoretical analysis.